Expectations and the Dynamics of Devaluation: A Comment - Burton, David (Review of Economic Studies, 1981)
Journal Article Expectations and the Dynamics of Devaluation: A Comment Get access David Burton David Burton Michigan State University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 4, October 1981, Pages 659–660, https://doi.org/10.2307/2297206 Published: 01 October 1981 Article history Received: 01 October 1980 Accepted: 01 March 1981 Published: 01 October 1981